Development and the challenge of dependency theory in Africa: a proposal for cultural humanism - Olatunji, F.; Cornelius A., U. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
The discourse on development is a fundamental issue as it affects everything that man does. It could be seen as a form of social change in which new ideas are introduced into a social system to produce higher and better living standards. In other words, it could be interpreted as man’s capacity to expand his own form of consciousness, awareness and power over himself and the society; that is, the optimum realisation of the well-being of individuals and the common good. It is the power of a people to solve their own problems with their own wisdom, experiences and resources. Dependency theory emerged as a result of the modernist theory’s limitation, which has a Marxian orientation. The major stand of the school is that development and under-development have dialectical relationship, that is, one leads to the other through the process of exploitations. The main factors responsible for development on one side and under-development on the other include the following: the pre-colonial trade, slavery, colonialism and neo-colonialism among others. These forces are characteristics of imperialism, which is a significant feature of capitalist expansion. The intent of this paper is to argue that there is always a cultural context to development, outside which a development change may not be appreciated. This paper, therefore, will submit that development would be meaningful when peoples’ choices, values and ideals are enlarged enough for them to acquire knowledge, have access to resources necessary for standard decent life and their active participation in community life. Key words: Dependency theory, development, Africa, values, Humanism